Klarspråk i nätinteraktion Trevlighet, trafikordningsplaner och undringar om döda rådjur i ett kommunalt e-serviceforum - Nord, Andreas (Klart språk i Norden, 2018)
I det svenska klarspråksarbetet har råd och riktlinjer för språket hittills varit anpassade för olika typer av traditionellt skriftspråkliga och monologiska texter, såsom informationstexter och beslutsbrev. Den nya typ av skriftlig kommunikation i olika digitala forum som börjar bli vanlig ställer krav på nya typer av råd och rekommendationer. För att veta mer om vilka råd och rekommendationer som ska utformas behöver vi dock veta mer om vad som faktiskt försiggår i sådana forum, och vilka kommunikationsproblem som kan uppstå. Artikeln bygger på en undersökning av interaktionen i ett internetforum på en svensk kommuns hemsida. Analysen visar att kommunikationen kännetecknas av en stark betoning av den relationella funktionen från kommunföreträdarnas sida, och denna ”trevlighet” fungerar av allt att döma väl. En utmaning verkar dock vara konflikten mellan vardagsvärld – här och nu – och regelstyrd myndighetsvärld, men analysen visar också att det inte nödvändigtvis är så enkelt att enskilda endast vill veta vad som gäller ”här och nu”. Summary In the ‘Plain Swedish’ effort, advice and guidelines have mostly focused on traditional written and monologic texts. This paper presents some results from a survey of the interactions between government employees and citizens in a Swedish municipality’s online forum, where citizens are invited to ask questions and seek advice. The findings represent a first step towards developing advice for written communication in the digital forums that are used by authorities to provide citizen services. The analysis shows that communication in the forums was characterised by a strong emphasis on the relational function or, in other words, on the relationship between the communicators manning the forum and the citizens. Seemingly, a focus on ‘niceness’ enabled the interactions to run relatively smoothly. One challenge, however, arose from the conflict between citizens’ life-world perspective and the rule-controlled government world. Citizens wish to find practical solutions to their problems in the here and now, and conflicts may occur when a specific question or request is simply answered by quoting the relevant regulation. The analysis, however, also shows that citizens were, in some cases, interested in knowing the underlying rules and regulations. This paper concludes by discussing the actual advantages of online forums for government-citizen interactions where repair in communications is possible.